Preambles and initial formulas in royal donations of the monastery of Leire: rhetoric and cultural relations (Edad Media. Revista de Historia, 2020)
The aim of this paper is to analyse a set of documents attributed to the first kings of Pamplona and conserved in the monastery of Leire. In particular, we have examined the literary sources of rhetorical preambles and initial formulas in order to draw conclusions regarding the circumstances that led to their inclusion.The analysis of these documents, mostly manipulated and falsified, has allowed us to prove the intense religious and cultural relationship between the Benedictine monastery of Leire and Aquitanian monasteries integrated into the Cluniac network. Such exchange can be considered as a consequence derived from the political, religious and cultural openness promoted by Sancho III the Great in the first half of the 11th century
Keywords: formulas; rhetoricism; ideology; literary sources; forgery